Tradition vs. traditionalism : contemporary perspectives in Jewish thought. - Sagi, Avi. (Value Inquiry Book Series, 2008)
This book is a first attempt to examine the thought of key contemporary Jewish thinkers on the meaning of tradition in the context of two models. The classic model assumes that tradition reflects lack of dynamism and reflectiveness, and the present's unqualified submission to the past. This view, however, is an image that the modernist ethos has ascribed to the tradition so as to remove it from modern existence. In the alternative model, a living tradition emerges as open and dynamic, developing through an ongoing dialogue between present and past. The Jewish philosophers discussed in this work-Joseph B. Soloveitchik, Yeshayahu Leibowitz, David Hartman, and Eliezer Goldman-ascribe compelling canonic status to the tradition, and the analysis of their thought discloses the tension between these two models. The book carefully traces the course they have plotted along the various interpretations of tradition through their approach to Scripture and to Halakhah.